FORMATION OF COMMUNICATIVE COMPETENCIES OF FUTURE IT SPECIALISTS - Burbekova, S. (Scientific Journal of Astana IT University, 2021)
The purpose of the study is aimed at performing a verification of the teaching conditions for effective communicative competence formation of the future IT professionals. Creating conditions of success, motivation enhancement, use of engaging group work, encouraging students’ participation in project work are the key factors and conditions for effective communicative competence formation. Scientific literature analysis, «communicative competence» concept clarification; analysis of pedagogical conditions of IT students’ communicative competence formation is discussed in details. Research methodology used is questionnaire, interview, quantitative and qualitative data analysis and processing of the results as well as analysis of class observation in AITU done within the IT students’ communicative competencies research. The national technological development strategy focuses both on the development of science-intensive technologies and technological cooperation and partnership. The need of society in IT specialists with a high personal and professional culture is determined by the need of a sufficient level of communicative competence to build professional relationships in workplace.